UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL UBI JALAR (IPOMOEA BATATAS L.) TERHADAP PERTUMBUHAN Escherichia coli dan Staphylococcus aureus - Atikah Fairus Siti Badriah; Febriana Dwi Wahyuni; Adri Nora (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Antibacterial is a compound capable of inhibiting and killing pathogenic bacteria. Escherichia coli and Staphylococcus aureus are pathogenic bacteria because they can cause disease if infected. Sweet potato is an alternative food that is often consumed by some Indonesian people and is thought to contain antibacterial compounds. The sweet potatoes used in this study came from Riau (A), Tomohon (B), Balikpapan (C), Jambi (D), Malang (E), Pontianak (F), Kupang (G), Bangka Belitung (H) , Medan (I), Balikpapan (J), and Merauke (K). Antibacterial testing was carried out using the disc diffusion method and using Eosin Methylene Blue (EMB) and Luria Bertani (LB) media with sample concentrations of 250, 500, and 700 ppm. The study was conducted using the antimicrobial activity testing method which was carried out only once in an experiment and observations would be made after 24 hours of incubation. From the results obtained, the optimum growth of E. Coli at a concentration of 700 ppm with samples from the Kupang area (G) with purple color with an inhibition zone of 8.5 mm and a minimum at a concentration of 250 ppm with samples originating from the Merauke (K) area with white color with a white zone. resistance of 1 mm. Meanwhile, the test results on the optimum growth of S. aureus at a concentration of 700 ppm with samples from West Kalimantan (F2) with purple color with an inhibition zone of 7 mm and a minimum at a concentration of 250 ppm with samples from Balikpapan (C), Bangka Belitung. (H), and Medan (I3) are white and light orange with an inhibition zone of 2 mm.